Visualizing the Emperor’s Pantheon: Images and Efficacy of Daoist and Buddhist Scripture Containers in the Qianlong Court - Zhan, Zhenpeng (Religion and the arts, 2022)
In the early 1740s, a set of carved lacquer containers were imperially commissioned in Suzhou to hold Daoist and Buddhist scriptures transcribed by the Qianlong emperor. Decorated with numerous deities in bas-relief, these understudied luxury objects shed new light on Buddhist and Daoist material cultures at the High Qing court and offer a glimpse of the imperial patron’s religious cosmology. Focusing on Qianlong’s two miniature pantheons and tracing the life history of objects in Qing palaces, this article explores the key role played by sacred images in elevating devotional objects of religious significance. As the most important offerings to Daoist and Buddhist deities, the lacquer boxes containing imperially transcribed scriptures were set on altars in different temples in the Forbidden City, even after Qianlong’s death. Characterized by rich religious symbolism, the Daoist and Buddhist icons designed for the containers embody visual efficacy that elevated the concealed scriptures and complemented the sacred spaces where they were enshrined.